Geospatial analysis of landslide susceptibility and safe relocation zones: Insights from recent disasters in Gofa Zone, Southern Ethiopia - Natnael Agegnehu Ayele; Esubalew Mulugeta Engda; Taye Teshome Terefe; Eyasu Leta; Talema Moged Reda; Muralitharan Jothimani (Quaternary Science Advances)
This study investigates landslide susceptibility and proposes potential relocation sites in the Gofa Zone of Southern Ethiopia, utilizing combined geospatial analysis techniques such as Geographic Information Systems (GIS) and Remote Sensing (RS). Factors such as slope, soil type, land use, rainfall, etc., were integrated into the analysis to identify the susceptible zones. A landslide susceptibility map was developed, categorizing the region into five susceptibility classes: very low, low, moderate, high, and very high. The analysis revealed that 11.74% of the Gofa Zone is classified as very low susceptibility, 31.33% falls under low susceptibility, and 30.02% is categorized as moderate susceptibility. Areas of high susceptibility cover 19.89%, while very high susceptibility zones account for 7.02% of the region. The findings indicate that high-risk areas are predominantly located in steep, mountainous terrains with unstable soils and intensive agricultural activities. In contrast, moderate and low-risk regions are characterized by more stable slopes and lower levels of human impact. Additionally, the study identifies potential relocation sites with minimal landslide risk, primarily located in flatter, stable terrains with less human encroachment. This study highlights the importance of combining GIS and RS for practical landslide risk assessment and provides valuable insights for disaster risk management, urban planning, and identifying safer areas for population relocation. The results are intended to assist local authorities and planners in making informed decisions to mitigate landslide hazards and promote sustainable regional development.